The Incidence of Central Serous Chorioretinopathy after Photorefractive Keratectomy and Laser In Situ Keratomileusis - Majid Moshirfar; Maylon Hsu; Julia Schulman; Joseph Armenia; Shameema Sikder; M. Elizabeth Hartnett (Journal of Ophthalmology)
Purpose. To assess the incidence of central serous chorioretinopathy (CSCR) following laser in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK). Methods. A chart review was performed to identify all patients with CSCR and a previous history of LASIK or PRK. Results. Over the 6-year study period, 1 of 4,876 eyes which had LASIK or PRK at the Moran Eye Center was diagnosed with CSCR. One other patient was referred from an outside center, developed CSCR symptoms one month after PRK. Both patients were managed conservatively with a final visual acuity of 20/20 or better. All other patients presented 4 or more years after refractive surgery. Conclusions. We report the first 2 CSCR cases developing within one month after PRK. The low incidence argues against a causal association. Topical corticosteroids or anxiety may elevate cortisol levels presenting therapeutic challenges for the management of CSCR after PRK or LASIK.